Enhancing Thermal Efficiency of a Solar Water Heating System with a Parabolic Trough Collector - Sukuria Mungkur, Rahmat; Umar, Hamdani; Abdullah, Nazaruddin; Amir, Fazri (Fakultas Teknik Universitas Samudra, 2024)
The growing population drives the construction of high-rise buildings as residential areas, leading to an increased demand for hot water for bathing, consumption, and other purposes. Conventional water heating using fossil energy negatively impacts the environment, making solar water heater (SWH) technology an eco-friendly alternative. However, the efficiency of conventional SWHs with evacuated tube collectors remains limited due to suboptimal solar energy capture. This study aims to enhance water heater efficiency by utilizing concentrated solar power (CSP) technology with a parabolic trough collector (PTC). The PTC focuses solar energy on a square-shaped receiver containing a sensible heat storage medium and a main pipe for heating water. The research was conducted experimentally by measuring water temperature with thermocouples and solar radiation using a pyranometer. The results show that the maximum water temperature achieved was 84°C at a solar radiation intensity of 1.112 W/m², with a maximum system efficiency of 35%. This technology demonstrates potential for improving the efficiency of renewable energy-based water heating systems.